Disturbed eating behaviors in adolescents with type 1 diabetes. How to screen for yellow flags in clinical practice?. Issue 5 (30th June 2016) - Eilander, Minke MA; de Wit, Maartje; Rotteveel, Joost; Aanstoot, Henk Jan; Bakker‐van Waarde, Willie M; Houdijk, Euphemia CAM; Nuboer, Roos; Winterdijk, Per; Snoek, Frank J
Abstract : Background: Adolescents with type 1 diabetes are at an increased risk of disturbed eating behaviors (DEBs). Objective: The aims of this study are to (i) explore the prevalence of DEBs and associated 'yellow flags', and (ii) establish concordance between adolescents–parents and adolescents–clinicians with respect to DEBs. Methods: Adolescents (11–16 yr) and parents completed questionnaires. A stepwise approach was used to assess DEBs: only adolescents whose answers raised psychological yellow flags for DEBs completed the Diabetes Eating Problems Scale – Revised and questions from the AHEAD study. Parents and clinicians shared their observations regarding possible DEBs. Kruskal–Wallis tests, post hoc Mann–Whitney U test, and chi‐squared tests were utilized to examine clinical yellow flags. Cohen's kappa was used to assess concordance. Results: Of 103 adolescents participated (51.5% girls), answers of 47 (46.5%) raised psychological yellow flags, indicating body and weight concerns. A total of 8% scored above cut‐off for DEBs. Clinical yellow flags were elevated glycated hemoglobin A1c (p = 0.004), older age (p = 0.034), dieting frequency (p = 0.001), reduced quality of life (p = 0.007), less diabetes self‐confidence (p = 0.015), worsened diabetes management (p < 0.001), and body dissatisfaction (p < 0.001). Body Mass Index (BMI) z‐scores and gender were no yellow flags. Concordance between parents and adolescents was slight (k = 0.126 and 0.141), and clinicians and adolescents was fair (k = 0.332). Discussion: Half of the adolescents reported body and weight concerns, less than 1 in 10 reported DEBs. Screening for yellow flags for DEBs as a part of clinical routine using a stepwise approach and early assistance is recommended to prevent onset or deterioration of DEBs.